Islam and Cultural Acculturation in Aceh: A Study of the Rah Ulee and Peulheuh Kaoy Rituals at the Tomb of Habib Seunagan - Cut Aja Mulia Aja Mulia; Darlin Rizki; Aviecenna Almaududy; Ahrijon (International Journal of Sharia and Law, 2025)
This study explores the phenomenon of Rah Ulee and Peulheuh Kaoy rituals at the tomb of Habib Muda Seunagan in Nagan Raya, Aceh, as a manifestation of cultural and religious acculturation between Islam and local traditions. The research adopts a descriptive qualitative approach through library research and field observation. Data were collected from books, journals, local articles, and interviews with the caretakers and community members around the tomb. The findings indicate that the Rah Ulee ritual, which involves symbolic washing of the head with sanctified water, and Peulheuh Kaoy, the act of releasing vows (nazar), are understood by the local community as forms of tawassul—seeking blessings through righteous figures. These practices are not merely cultural but have been integrated into the spiritual and social fabric of Acehnese Islam. While some religious groups perceive these rituals as deviations from Islamic orthodoxy, many locals consider them expressions of reverence and continuity of spiritual heritage rooted in Sufism, particularly the Syattariyah order introduced by Habib Muda Seunagan. Thus, these rituals exemplify how Islamic teachings and Acehnese culture coexist harmoniously through a process of acculturation that strengthens community identity and religious devotion.